Strategies for Handling Problematic Murabaha Financing at Bank Syariah Indonesia Cipto Sub Branch Office - Mulyana, Rijal Assidiq; Maharani, Silviya (Etihad: Journal of Islamic Banking and Finance, 2023)
Introduction: The large public interest in murabahah financing at Shariah Bank requires the bank to have a strategy for handling problematic financing. The research was conducted at Bank Syariah Indonesia Cipto Cirebon Sub Branch Office to describe the strategy for handling problematic murabaha financing. Research Methods: The research method used was a qualitative method with a case study approach trough observation, structured interviews, and documentation techniques Results: The results obtained indicate that the causes of problematic murabahah financing at Bank Syariah Indonesia Cipto Cirebon Sub Branch Office are not only due to internal factors of the bank but also external factors from the customers themselves, such as the customer's uncontrollable lifestyle, the customer's job loss, the customer's application for another financing, the customer's poor character, and the customer's employment in a less reputable company. The strategy for handling problematic murabahah financing at BSI KCP Cipto Cirebon is to use the prudential principle, which is by analyzing potential customers using the 5C principles, visiting customers' homes, sending warning letters, and the last sending collateral surrender letter. Meanwhile, efforts to prevent problematic business financing carried out by BSI KCP Cipto Cirebon are by forming a financing committee that aims to analyze and evaluate financing, discuss with all financing units, and avoid the causes of previous financing problems. Conclusion: The research findings are expected to serve as a basis for discussion to discover and formulate the best approach in handling problematic murabaha financing cases.